Penegakan Hukum Pidana terhadap Penyebaran Rokok Ilegal di Indonesia - I Made Citra Yudistira (Perspektif Administrasi Publik dan hukum, 2026)
The circulation of illegal cigarettes constitutes a serious problem that results in state financial losses and disrupts legal certainty in the excise sector. Although criminal provisions related to the circulation of illegal cigarettes have been explicitly regulated in statutory laws, law enforcement practices demonstrate a tendency to apply administrative sanctions rather than criminal sanctions. This study aims to analyze the regulation of criminal law concerning illegal cigarette circulation and to examine the implications of the dominance of administrative sanctions on the effectiveness of criminal law. The research employs a normative juridical method using statutory and conceptual approaches through library research on primary and secondary legal materials. The findings indicate that the main problem does not lie in the absence or contradiction of legal norms, but in the emergence of vague norms at the implementation level due to inconsistent application of criminal sanctions. This condition weakens legal certainty, reduces the deterrent effect of criminal law, and undermines the protection of public interests. This study emphasizes the importance of consistent application of criminal sanctions to ensure that criminal law functions effectively in addressing illegal cigarette circulation.